Diversity and feeding strategies of soil microfauna along elevation gradients in Himalayan cold deserts - Devetter, Miloslav; Háněl, Ladislav; Řeháková, Klára; Doležal, Jiří (PloS one, 2017)
High-elevation cold deserts in Tibet and Himalaya are one of the most extreme environments. One consequence is that the diversity of macrofauna in this environment is often limited, and soil microorganisms have a more influential role in governing key surface and subsurface bioprocesses. High-elevation soil microfauna represent important components of cold ecosystems and dominant consumers of microbial communities. Still little is known about their diversity and distribution on the edge of their reproductive and metabolic abilities. In this study, we disentangle the impact of elevation and soil chemistry on diversity and distribution of rotifers, nematodes and tardigrades and their most frequent feeding strategies (microbial filter-feeders, bacterivores, fungivores, root-fungal feeders, omnivores) along two contrasting altitudinal gradients in Indian NW Himalaya (Zanskar transect from 3805 to 4714 m a.s.l.) and southwestern Tibet (Tso Moriri transect from 4477 to 6176 m a.s.l.), using a combination of multivariate analysis, variation partitioning and generalized additive models. Zanskar transect had higher precipitation, soil moisture, organic matter and available nutrients than dry Tso Moriri transect. In total, 40 species of nematodes, 19 rotifers and 1 tardigrade were discovered. Species richness and total abundance of rotifers and nematodes showed mid-elevation peaks in both investigated transects. The optimum for rotifers was found at higher elevation than for nematodes. Diversity and distribution of soil microfauna was best explained by soil nitrogen, phosphorus and organic matter. More fertile soils hosted more diverse and abundant faunal communities. In Tso Moriri, bacterivores represented 60% of all nematodes, fungivores 35%, root-fungal feeders 1% and omnivores 3%. For Zanskar the respective proportions were 21%, 13%, 56% and 9%. Elevational optima of different feeding strategies occurred in Zanskar in one elevation zone (4400-4500 m), while in Tso Moriri each feeding strategy had their unique optima with fungivores at 5300 m (steppes), bacterivores at 5500 m (alpine grassland), filter-feeders at 5600 m and predators and omnivores above 5700 m (subnival zone). Our results shed light on the diversity of microfauna in the high-elevation cold deserts and disentangle the role of different ecological filters in structuring microfaunal communities in the rapidly-warming Himalayas.
Keywords: houby; Biodiversity; Cold Temperature; Nepál; nadmořská výška; nízká teplota; ekosystém; Soil; Altitude; Ecosystem; Fungi; Bacteria; Tibet; biodiverzita; Nepal; půda